STRATEGI ASWAJA NU CENTER DALAM MENANGKAL RADIKALISME DI LEMBAGA PENDIDIKAN ISLAM: Studi Kasus di Kepung Kediri - Lilik Nur Latifah (Jurnal Penelitian Ilmiah INTAJ, 2025)
The influx of radical ideology into Islamic educational institutions has become a serious concern in the context of nationalism and Islam. This study aims to examine the strategies implemented by the Aswaja NU Center (MWC NU) in Kepung District, Kediri Regency, to counter the spread of radicalism in educational settings. Using a qualitative approach and field case study methods, data were collected through in-depth interviews, participant observation, and documentation. The results show that the Aswaja NU Center responded to this ideological challenge by building an educational ecosystem based on the values ​​of Aswaja An-Nahdliyah through five main programs and eleven concrete activities. This strategy is not confrontational, but rather educative, participatory, and oriented towards strengthening the ideological awareness of educational actors. This article concludes that local, tradition-based forces have a transformative capacity to sustainably stem radical ideology.